Digital Da’wah Communication Strategies in Shaping Muslim Family Morals in the Technological Era - Pratiwi, Anjeli; Cahyani, Andini Nandea (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study aims to examine the strategies of digital da’wah communication in shaping the moral values of Muslim families in the technological era. The rapid development of digital media has transformed the pattern of Islamic preaching (da’wah) from traditional face-to-face methods into broader, faster, and more interactive approaches through various platforms such as social media, messaging applications, and audio-visual content. This research employs a library study method by reviewing academic literature, scientific articles, and relevant journals published within the last ten years. The findings reveal that digital da’wah plays a crucial role in strengthening the moral foundations of Muslim families, which include faith, ethics, parental responsibility, harmonious communication, and self-control. Effective communication strategies involve persuasive language, appropriate media selection, and the use of creative content contextualized to the needs of modern Muslim families. Moreover, collaboration between preachers, religious figures, and Islamic institutions through digital media has proven to expand the reach of da’wah while enhancing community engagement. The study also highlights that the success of digital da’wah strategies depends on the ability of preachers to adapt messages to audience characteristics without neglecting Islamic principles. Therefore, digital da’wah functions not only as a medium of religious information dissemination but also as a means of fostering the moral integrity of Muslim families in facing the challenges of globalization and technology.